Analisis Faktor Yang Berhubungan Dengan Aktivitas Sosial Lansia Di Masyarakat - Wahyuni, Endang Sri; Arifiati, Retna Febri (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Improving social relationships in the elderly. However, the level of elderly participation in social activities is influenced by demographic characteristics such as age, gender, education level, and economic status. This study aims to analyze the relationship between demographic factors and social activities of the elderly.Research Methods: This study uses a quantitative method with a cross-sectional design. Data were collected through questionnaires distributed to 41 elderly people. The research instrument was the Social Activity Scale (SAS). Data analysis was performed using crosstabulation analysis to identify the relationship between demographic variables and social activity.Research Results: The results showed that the majority of respondents had social activity at the "medium" level (70.7%) and 29.3% had "high" social activity. There was a downward trend in social activity with age. The gender factor showed that men had more "high" social activities than women. Education level also had a significant effect; the higher the education level, the more the elderly engaged in "high" social activities. Seniors with a junior high school education or higher tended to have a more even distribution of social activities between "moderate" and "high".Conclusion: Demographic characteristics have a significant influence on the level of social activity of the elderly.